The incidence and risk factors for development of lower limb lymphedema after treatment for gynaecological cancers - Khalid, Noori; Dharmarajan, Adarsh; B., Satheeshan; M. S., Biji; S. S., Abina; Binesh, Remya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The development of postoperative lower limb lymphedema (LLL) is a disabling, yet usually overlooked sequele of most gynecological cancer treatment. It can lead to significant functional problems that negatively affect gynecological cancer survivors’ daily living, work, emotional state, and overall quality of life. The objective of this study is to calculate the incidence of lower limb lymphedema in patients undergoing surgery for gynecological cancer and to evaluate the risk factors for its development. Methods: Women with newly diagnosed carcinoma ovary, carcinoma endometrium and carcinoma cervix, who underwent surgery at a tertiary cancer centre from September 2016 were included in the study. The circumference of both lower limbs was measured at prefixed sites. The limb volume was calculated using the formula C2/pi. A baseline value was taken prior to surgery. The patients were followed up every 3 months and the limb volume were calculated at each visit. An increase in limb volume by >10% was defined as lymphedema. Results: The incidence of lymphedema after 1 year follow up was 43.5%. There was no significant association between known risk factors such as extent of lymphadenectomy (p value 0.633) number of pelvic or para aortic lymph nodes removed (p value 0.69 and 0.44 respectively) and type of adjuvant therapy (p value 0.455). Conclusions: The incidence of LLL according to the present study was 43.5%. There was no statistically significant association between development of LLL and risk factors like site and number of lymph nodes removed and type of adjuvant therapy.